Communities of mites (Acari) in litter and soil under the invasive red oak (Quercus rubra L.) and native pedunculate oak (Q. robur L.) - Kohyt, Joanna; Skubała, Piotr (Biological Letters, 2014)
Because of thoughtless decisions or unintentional introduction, alien species disturb native ecosystems. Red oak (Quercus rubra), among other alien woody plants, is still used to rehabilitate degraded land because of its better resistance to pollution and faster growth, as compared to native tree species. Soil mites, especially Oribatida, are good bioindicators of ecosystem disturbance, so the main goal of this study was to explore the influence of invasive and native oaks on mite communities. F orest stands dominated by 40-year-old Q. rubra or 35-year-old Q. robur were compared. Over 2300 soil mites were extracted from 20 soil and 20 litter samples. M ite densities in the communities were higher in red oak litter, which is probably a result of the thicker layer of shed leaves. Changes in species composition of oribatid communities were observed in litter, in contrast to a lack of differences in soil. These observations are consistent with other researches on invasive woody plants. W e expect that over time these changes will also be noticeable in the soil and will increase in litter.